Family farming in international law - Srogosz, Tomasz (Przegląd Prawa Rolnego, 2024)
Thirty years ago, Professor Aleksander Lichorowicz wrote about family farming in the age of expanding agribusiness. The topic is still relevant today, both from the perspective of national, EU and international law. However, it has not been considered in the Polish literature from the perspective of an internationalist lawyer. In particular, it is therefore worth asking the question of the impact of national laws on the domestic policy towards family farming. The article undertakes an analysis of the WTO's agricultural law and policy and their impact on the activities of the Bretton Woods and IFAD institutions. At the same time, initiatives standing in opposition to the concept of agribusiness promoted within the WTO are presented. Of importance here is the identification of the impact of Via Campesina on the development of soft law under the auspices of the UN and FAO. It turns out that the development of soft instruments contributes to the growing importance of family farming at the international level, which does not necessarily entail a break with the direction pushed by the WTO. The remedy for this state of affairs would be to consider developing an international agreement on the protection of family farming.